Primary health problems in rural school children in Lebanon - Helou, Mariana C. (2017)
Background: Primary health problems among school children are rarely disaggregated between urban and rural areas. This report describes findings in children examined during school health visits in a rural region in South Lebanon. Methods: Medical visits were carried out in four public schools in the Qana region, district of Sour, between December 2007 and May 2008. Results: A total number of 887 students were examined. Age varied between 4 and 16 years old. The majority (78%) had a normal weight for their age. Around 7.1 % of males and 3.5 % of females were considered obese for their age. The most frequent abnormality found was dental caries (59%). In addition, 14% of students had cerumen earplugs, and 3.6% had untreated defective visual acuity. Cases of pediculosis (n=62) were found in just one school, indicating a local outbreak of limited scope. Conclusions: There were only minor differences between health problems in this rural area and those measured in an urban area 10 years earlier. Dental problems continued to be predominant. In future campaigns, health education sessions should be conducted about personal hygiene and adequate nutrition with students, teachers and/or parents, in parallel to conducting the medical visits.